Personality and Parenting Behavior II: Fathers of Croatian Adolescents - Brković, Irma (Array, 2006)
Personality traits in transaction with environment produce characteristic adaptations and interpersonal relationships. Individual differences in personality manifest themselves in a wide range of behaviors including parental behavior. Although the empirical evidence on relationship between personality traits and quality of parenting indicate several significant relationships, they are still limited and inconsistent. In addition most research focuses on mothers than fathers and on parents of young children than of older children. Some research indicate that personality traits predict fathering weaker than mothering and that somewhat different personality dimensions are related to the parenting of fathers than on mothers. This study examines the relationship between big-five personality traits of more than 800 fathers of adolescents and their parenting behavior as assessed by themselves and their children. In addition, possible child (age and gender) and father (age and education) moderators of personality-parenting association are examined. Paternal personality was assessed by IPIP Five Factor Personality Inventory (Goldberg, 1999) that consists of 50-items and measures the domains of the Five Factor Model (Costa & McCrae, 1992): openness, conscientiousness, extraversion, agreeableness and neuroticism. Parenting was assessed by means of 33-item Croatian Parental Behavior Questionnaire (Kerestes & Kuterovac Jagodic, 2005) that measures seven dimensions of parenting: acceptance, rejection, permissiveness, psychological control, monitoring, positive discipline and negative discipline. Mean age of the fathers was 42 years and of the children 12.6 years. The differential role of personality traits in predicting different aspects of parenting as moderated by the father’ s and the child’ s variables will be discussed